Impact of health spending on hospitalization rates in Baltic countries: a comparative analysis - Huan Jiang; Alexander Tran; Inese Gobiņa; Janina Petkevičienė; Rainer Reile; Mindaugas Štelemėkas; Ricardas Radisauskas; Shannon Lange; Jürgen Rehm (BMC, 2024)
Abstract Introduction This study examines the association between healthcare indicators and hospitalization rates in three high-income European countries, namely Estonia, Latvia, and Lithuania, from 2015 to 2020. Method We used a sex-stratified generalized additive model (GAM) to investigate the impact of select healthcare indicators on hospitalization rates, adjusted by general economic status-i.e., gross domestic product (GDP) per capita. Results Our findings indicate a consistent decline in hospitalization rates over time for all three countries. The proportion of health expenditure spent on hospitals, the number of physicians and nurses, and hospital beds were not statistically significantly associated with hospitalization rates. However, changes in the number of employed medical doctors per 10,000 population were statistically significantly associated with changes of hospitalization rates in the same direction, with the effect being stronger for males. Additionally, higher GDP per capita was associated with increased hospitalization rates for both males and females in all three countries and in all models. Conclusions The relationship between healthcare spending and declining hospitalization rates was not statistically significant, suggesting that the healthcare systems may be shifting towards primary care, outpatient care, and on prevention efforts.